IMPROVING TEACHERS' UNDERSTANDING OF INCLUSIVE EDUCATION - Rosyidah, Ulfiyyatur; Rindanigsih, Ida (Antis-Publisher, 2024)
The existence of inclusive education in Indonesia plays a central role in achieving equitable and inclusive education for all students. This article identifies and formulates problems related to teachers' low understanding of the concept of inclusion, limited resources and variations in understanding of the concept of inclusion among educators. These challenges create barriers to the effective implementation of inclusive education across educational institutions. Through an in-depth literature review and analysis, this article offers a number of solutions, including improved teacher training programs, collaboration between stakeholders and improved access to inclusive learning information and resources. It concludes that changes need to be made at the policy, education institution and community levels to create a sustainable inclusive education environment that benefits all students in Indonesia. As such, this article contributes to an in-depth understanding of the challenges and solutions in the context of inclusive education in Indonesia.